After 20 Years on the Market: The Current Outlook on E-Cigarette Use Among Youth - Drewnowska, Katarzyna; Modrzewski, Jakub; Radziszewska, Julia; Drozd, Agata; Kościelniak, Agata; Danielewicz, Klaudia; Rypińska, Agata; Kupczyk, Zofia; Kuźmiuk, Julia; Piskorowska, Klaudia; Kreft, Łukasz (Journal of Medical Science, 2025)
Introduction. Electronic nicotine dispensing systems, commonly known as e-cigarettes, remain the most widely used tobacco product among the youth, with current worldwide use estimated at approximately 5 to 7%. Nevertheless, several aspects of knowledge on their sustained consumption are based on suppositions, such as their role as a “gateway” into cigarette smoking for new generations and the potential subsequent renormalisation of tobacco use. Moreover, recent clinical trials and toxicological assessments have yielded noteworthy findings, revealing their potential to cause tissue damage in the lungs, heart, and oral cavity.